Evidence-based policy-making: achieving destination competitiveness in Malta - Mangion, Marie-Louise (2011)
This thesis explores how tourism policy, if based on evidence, can contribute to the objective of destination competitiveness. Evidence-based policy-making is informed by high-quality research formulated using rigorous, scientific methods. The thesis aims to show that policy analysis applied to the macro and micro levels can create evidence for use in policy formulation. The research is set within the Mediterranean context, with particular emphasis on Malta’s competitiveness within the inclusive tour holiday market originating from the United Kingdom.